Knowledge of Improved Cultivation Practices of Rose Grown by theFarmers of Khamnor Panchayat Samiti District of Rajsamand, Rajasthan (Indian Journal of Extension Education, 2010)
Rose is most important cut-flower. It occupies the first position in the foreign trade of cut-flower followed by Chrysanthemum and carnation. More than 140 countries are involved in the world floriculture trade. Netherland is the largest producer as well as the exporter of the cut-flowers (63 per cent) in the world. Germany, on the other hand is the largest importer. Its share in the world import has been around 37 per cent.